2018
DOI: 10.1038/s41467-018-05915-w
|View full text |Cite|
|
Sign up to set email alerts
|

Engineered bidirectional promoters enable rapid multi-gene co-expression optimization

Abstract: Numerous synthetic biology endeavors require well-tuned co-expression of functional components for success. Classically, monodirectional promoters (MDPs) have been used for such applications, but MDPs are limited in terms of multi-gene co-expression capabilities. Consequently, there is a pressing need for new tools with improved flexibility in terms of genetic circuit design, metabolic pathway assembly, and optimization. Here, motivated by nature’s use of bidirectional promoters (BDPs) as a solution for effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 70 publications
1
116
0
Order By: Relevance
“…We investigated promoters from R. toruloides that were posited to have medium or strong transcriptional activity in both directions. Bidirectional promoters can reduce design and assembly complexity and also help keep DNA construct sizes within reasonable limits, a useful feature when engineering multigene pathways [20][21][22]. Of the 14 promoters that were predicted to be bidirectional according to RNA-sequencing data (P1, P2, P8, P9, P11, P12, P13, P19, P21, P22, P24, P25, P28 and P29) fluorescence of both reporters was detected for 8 of them, indicating bidirectional transcription (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated promoters from R. toruloides that were posited to have medium or strong transcriptional activity in both directions. Bidirectional promoters can reduce design and assembly complexity and also help keep DNA construct sizes within reasonable limits, a useful feature when engineering multigene pathways [20][21][22]. Of the 14 promoters that were predicted to be bidirectional according to RNA-sequencing data (P1, P2, P8, P9, P11, P12, P13, P19, P21, P22, P24, P25, P28 and P29) fluorescence of both reporters was detected for 8 of them, indicating bidirectional transcription (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid clonal variation due to different copy numbers of integrated expression cassettes as well as different integration sites and genomic alterations that can bias expression strength comparisons in P. pastoris (Schwarzhans et al 2016a, b;Vogl et al 2018a), transformants from this study underwent the following screening and rescreening procedures [the section is adapted from the open access publication (Vogl et al 2018b)]. P. pastoris cells were transformed with molar equivalents to 1 µg of the empty pPpT4_S vector SwaI linearized plasmids as 1 µg of the empty pPpT4_S vector was found to yield predominantly single copy integration (Vogl et al 2014(Vogl et al , 2018a.…”
Section: Screening Rescreening Procedures and Culture Conditionsmentioning
confidence: 99%
“…(Hartner et al 2008;Vogl et al 2018c)]. P PpAOX1 variants (Hartner et al 2008), alternative promoters (Prielhofer et al 2013), novel MUT promoters , synthetic bidirectional promoters (Vogl et al 2018b) and altering the molecular regulation of P PpAOX1 (Shen et al 2016a, b;Wang et al 2017;Vogl et al 2018c) showed derepression to varying extents in P. pastoris.…”
Section: Introductionmentioning
confidence: 99%
“…To engineer the second module, SMO genes ( styAB ), SOI gene ( styC ) and PAR gene had been engineered together with SMO_SOI to give SMO_SOI_PAR. To obtain balanced enzyme expression in the E. coli strains, many strategies could be employed, such as engineering the promoters or the ribosome‐binding sites of the genes. Herein, we utilized four plasmids with different copy numbers to optimize the co‐expression: each of module was constructed in pACYC, pCDF, pET, and pRSF, respectively.…”
Section: Resultsmentioning
confidence: 99%